WELLBEING CONDITION OF INTERNATIONAL MIGRANT WORKERS FROM INDONESIA WHO WORKED IN MALAYSIA: STUDY ON INTERNATIONAL MIGRANT WORKERS FAMILY IN KRANGKENG SUB-DISTRICT INDRAMAYU REGENCY WEST JAVA PROVINCE INDONESIA - Dwi Yuliani; Uke Hani Rasalwati (Politeknik Kesejahteraan Sosial Bandung, 2020)
The industrial revolution 4.0 has human resources that move between Indonesian workers to Malaysia. This research was conducted to find an understanding of the wellbeing condition of families of Indonesian international migrant workers who work in Malaysia. The research was conducted using quantitative descriptive method. The research respondents were 71 families of international migrant workers. Data collection techniques used questionnaires. Data analysis techniques used descriptive statistical analysis.The results showed that the problems faced by families of international migrant workers from Indonesia working in Malaysia included; (1) disruption of the fulfillment of husband / wife's love needs; (2) disruption of family economic needs; (3) disruption of the care function of children under five years of age (toddlers); (4) the disruption of the fulfillment of children's needs.The efforts made by families of international migrant workers from Indonesia who worked in Malaysia in overcoming their problems include; (1) resigned; (2) asking for large family assistance; (3) forgetting for a better future; and (4) trying to work to find additional income.The result of research on the psychosocial condition of family indicated; (1) families feel anxious in living life; (2) loneliness in living life; (3) difficulty sleeping; (4) anxiety; (4) more irritable and lose patience; (5) often sad; (6) concentration is disrupted when carrying out daily activities; (7) low self-esteem when meeting relatives; and (8) low self-esteem when interacting with neighbors / environment.Related to the socio-economic condition of the families of international migrant workers, the result showed that; (1) the participation of family members in participating in activities in the local environment is low; (2) the fulfillment of family members' food needs is fulfilled; (3) fulfillment of family member's clothing requirement is fulfilled; (4) increase of assets and family ownership is no change; (5) meeting the needs of the social environment and family residence is less fulfilled; (6) meeting the health needs of family members is less fulfilled; (7) the fulfillment of family members' education needs is less fulfilled. Recommended programs through the formation of a Self Help Group.This Self Help Group is a collection of various families of international migrant workers working in Malaysia. In its implementation, this Self Help Group serves as a container and means of families of international migrant workers to experience various experiences in handling problems faced by their families.